Answer:/
I,,,,M SORRYI NEED POINTSSS
Step-by-step explanation:
Answer:
x - intercept = 6
y - intercept = 3
Step-by-step explanation:
To find x - intercept, substitute y = 0 in the equation and solve for x.
x = 6
Similarly, To find y - intercept, substitute x = 0 in the equation and solve for y.
y = 3
Answer:
X = -2 and 4
Step-by-step explanation:
Move all of the terms to one side and set the equation to 0:
2x^2-14x+40-3x^2+16x-32 = 0
Then combine all like terms which would look like the following:
-x^2 + 2x + 8=0
Change the signs on both sides of the equation:
x^2 - 2x - 8 =0
Write -2x as a difference:
x^2 + 2x - 4x -8 = 0
Factor the expression:
x(x+2) x 4(x+2)=0
Factor out x+2 from the equation:
(x+2) (x-4)=0
Split into classes and then find the answer from there:
x+2=0
x-4=0
Answer:
18
Step-by-step explanation:
David=x
Michelle=x-2
Karen=x-2+6=x+4
sum of ages=62
x+x-2+x+4=62
3x=60
x=20
age of Michelle=20-2=18
Answer:
179
Step-by-step explanation:
39*(15/3)-16
39*5-16
195-16
179